Association between job satisfaction and organizational commitment among physicians who treated patients during the COVID-19 pandemic at the Hospital Nacional Daniel Alcides Carrión, 2020–2021 - Robles Cuadros, Juan Martín (2024)
Objective: To determine the association between organizational commitment and job satisfaction among physicians who treated COVID-19 patients at the Hospital Nacional Daniel Alcides Carrión from 2020 to 2021. Materials and methods: A cross-sectional and analytical study which involved 194 physicians. Job satisfaction and organizational commitment were measured using the Minnesota Satisfaction Questionnaire and Meyer and Allen’s Three Component Model of Commitment. Based on the scores and the Likert scale, the variables were categorized as high, medium or low. Results: Seventy-one percent of physicians reported intrinsic job satisfaction and 93 % exhibited affective organizational commitment and continuity at the hospital. Physicians with a strong sense of achievement were 2.71 times more likely to experience job satisfaction and feel proud to work at the institution (CI: 1.05-7.03). Physicians satisfied with the treatment they received from their chief and wishing to remain at the institution were associated with an OR of 3.26 (CI: 1.50-7.24). Agreement with institutional policies and a sense of loyalty to the institution had an OR of 3.25 (CI 1.40-17.23). Self-taught physicians who felt that they owed a lot to the institution had an OR of 2.55 (CI: 1.31-4.94). Multivariate analysis showed higher job satisfaction among males (OR: 2.40 [CI: 1.15-5.00]), those receiving full personal protective equipment (OR: 9.68 [CI: 3.01-31.12]) and those who obtained timely economic incentives (OR: 4.52 [CI: 1.76-11.53]). Conclusions: Job satisfaction is directly proportional to physicians’ organizational commitment. The greater the job satisfaction among employees, the higher their commitment to their institution. Likewise, being male, receiving full personal protective equipment and obtaining timely economic incentives were strongly associated with higher job satisfaction.